Association of immature stages of some caddisfly species from northwestern Argentina with description of a new species of Helicopsyche (Trichoptera: Helicopsychidae) - Martín, Paola A. Rueda; Miranda, Águeda Verónica Isa (Zootaxa, 2015)
The adult, larva, and pupa of Helicopsyche obscura sp. nov. from northwestern Argentina are described and illustrated. Descriptions and illustrations of adults and associated pupae and larvae of Helicopsyche turbida Navás and Leptonema boliviense boliviense Mosely are included. The associations of immature stages were made using the metamorphotype method. Helicopsyche turbida is newly recorded from Tucumán province. The adult males of H. obscura sp. nov. and H. turbida have similar structure in the genital segments, however, the most clear differences are in the general color and size of the adult, and in the color, size, and morphology of the metanota in the larval stages as well as the shapes of mandibles, hook plates, and terminal segments of the pupal stages. The larva and pupa of L. boliviense boliviense are compared with those of L. columbianum and other previously described species, providing differences in color, chaetotaxy, and morphology.